RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MACROMEDIA PADA MATA PELAJARAN SIMULASI DIGITAL - Anwar Yusuf; Efrizon Efrizon (Universitas Negeri Padang, 2019)
Digital Simulation is a basic subject of expertise in curricula in 2013. This Digital Simulation Learning is more directed at the activities of knowledge and skills for all students to shape their creativity by networking information with other parties who function to improve their knowledge and skills. In this research discusses the design of interactive learning media based on Macromedia on digital simulation subjects at 1 Baktiya Vocational School. In this design use the classic tutorial model. The software used to create media is Macromedia Adobe Director 11.5 and other supporting applications. The existence of pretest in the media as a measure of students' knowledge of the material being studied. Based on the results of the validity test the media obtained an average score of 0.83 so that the media is worthy of use. It is hoped that this media can become an example for designing interactive media, so that students are motivated while learning, and the achievement of learning objectives. Keywords: Designer, Interactive Learning Media, Adobe Director.